The Genetics of Leaf Flecking in Maize and Its Relationship to Plant Defense and Disease Resistance . Issue 3 (26th September 2016) - Olukolu, Bode A.; Bian, Yang; De Vries, Brian; Tracy, William F.; Wisser, Randall J.; Holland, James B.; Balint-Kurti, Peter J.
Abstract : Leaf flecking in maize may be related to disease resistance and to a diverse set of metabolic pathways. Abstract: Physiological leaf spotting, or flecking, is a mild-lesion phenotype observed on the leaves of several commonly used maize ( Zea mays ) inbred lines and has been anecdotally linked to enhanced broad-spectrum disease resistance. Flecking was assessed in the maize nested association mapping (NAM ) population, comprising 4, 998 recombinant inbred lines from 25 biparental families, and in an association population, comprising 279 diverse maize inbreds. Joint family linkage analysis was conducted with 7, 386 markers in the NAM population. Genome-wide association tests were performed with 26.5 million single-nucleotide polymorphisms (SNP s) in the NAM population and with 246, 497 SNP s in the association population, resulting in the identification of 18 and three loci associated with variation in flecking, respectively. Many of the candidate genes colocalizing with associated SNP s are similar to genes that function in plant defense response via cell wall modification, salicylic acid- and jasmonic acid-dependent pathways, redox homeostasis, stress response, and vesicle trafficking/remodeling. Significant positive correlations were found between increased flecking, stronger defense response, increased disease resistance, and increased pest resistance. A nonlinear relationship with total kernel weight also was observed whereby lines with relatively high levels of flecking had, on average, lower total kernel weight. We present evidence suggesting that mild flecking could be used as a selection criterion for breeding programs trying to incorporate broad-spectrum disease resistance.